Antioxidant and Antibacterial Activities of Ethanol Extract of Matoa (Pometia pinnata) Leaves - Razoki Razoki (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
A Plants used for traditional medicine are matoa (Pometia pinnata). This plant is spread in almost every area in the province of Papua. The use of plants as medicinal ingredients is closely related to the content of chemical compounds contained in these plants, especially related to the active compounds contained in plants. Based on previous research, matoa leaf extract contains alkaloids, flavonoids, steroids, tannins, glycosides, and saponins. This study aims to determine the antioxidant and antibacterial activity of Pometia pinnata leaf extract. In the early stages of this research, the extraction process was carried out using the reflux method using ethanol solvent, testing the antioxidant activity using the DPPH and ABTS methods, as well as total phenol and flavonoids. Meanwhile, testing the antibacterial activity with the Minimum Inhibitory Concentration method against Staphylococcus aureus and Pseudomonas aeruginosa. From the results of the antioxidant activity test, the IC50 value was obtained in the DPPH method of 41.83 ± 0.17 µg/mL and also in the antibacterial test, it could inhibit the growth of Staphylococcus aureus and Pseudomonas aeruginosa bacteria